Shaggy aorta-An autopsy analysis - Pranita Zare; Pradeep Vaideeswar (Wolters Kluwer Medknow Publications, 2024)
Aims: Shaggy aorta is defined as "very extensive atheromatous disease with diffuse ulcers associated with soft, loosely held debris and a paucity of actual thrombus" and often results in visceral or peripheral arterial embolization (shaggy aorta syndrome). Most of the studies are clinico-radiological with hardly any assessment of the pathological features. We present an autopsy analysis of shaggy aorta. Materials and Methods: A retrospective study of autopsied cases of shaggy aorta over 15 years was conducted. The involvement of the various segments of the aorta (ascending, transverse, thoracic, and abdominal) was correlated with the clinical manifestations and cardiac/extra-cardiac findings at autopsy. The mortality was categorized as those related to shaggy aorta (Group I), related to cardiac diseases (Group II), and those unrelated to cardiovascular diseases (Group III). Statistical Analysis: Nil. Results: In a span of 15 years, there were 76 cases of shaggy aorta affecting predominantly males (85.5%) and patients in the sixth decades of life (mean age of 64.5 years). The important associated cardiovascular risk factors included hypertension, tobacco use, and diabetes mellitus. Predominant involvement of the entire aorta and arch + descending aorta was seen in 39.5% and 35.5% of the cases, respectively. Regardless of extreme severity, only half of the patients (37 cases, 48. 7%) had clinical presentation due to shaggy aorta. Conclusions: The occurrence of shaggy aorta may be more common than expected, and it would be important to keep this possibility in mind even in asymptomatic elderly patients with cardiovascular risk factors since aorto-arterial manipulations and anti-coagulant therapy can prove detrimental in such patients.